Honour thy Father - Murphy, Elizabeth (London Headline, 1996)
From the author of A WISE CHILD and THERE IS A SEASON, a novel in which a young woman struggles to gain a deeper understanding of her mother and father's relationship. It is not until she marries a man whose temperament is different to her own, and has a family of her own that she gains a fuller understanding of her parents' lives.
Keywords: England--Liverpool -- Fathers and Daughters -- Families